Association between kratom (Mitragyna speciosa) use and metabolic syndrome - Aroon La-up (Heliyon, 2022)
Background and aims: There are evidence about effects of kratom (Mitragyna speciosa) use on parameters related to metabolic syndrome (MetS). The present study aimed to determine the association between kratom use and MetS. Methods: This study is a cross-sectional study of 581 subjects (kratom users and non-users) aged 18 and over from the Nam Phu sub-district, Surat Thani province, Thailand. The association was determined using multivariate logistic regression. Results: MetS prevalence in kratom users and non-users was 11.9% (95% CI, 8.4–16.3%) and 21.6 % (95% CI, 17.1–26.8%), respectively. The use of kratom was associated with the lower odds of MetS (adjusted OR, 0.56; 95% CI, 0.33–0.96). Kratom use were associated with smaller waist circumference, lower triglycerides, and higher high-density lipoprotein. Conclusions: The current study demonstrated a potential protective effect of kratom use against MetS.